2017
DOI: 10.1016/j.jpeds.2016.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Inflammatory-Associated Proteins in the First Month of Life and Cognitive Impairment at Age 10 Years in Children Born Extremely Preterm

Abstract: Objectives To evaluate whether in children born extremely preterm, indicators of sustained systemic inflammation in the first month of life are associated with cognitive impairment at school age. Study design 873 of 966 eligible children previously enrolled in the multicenter Extremely Low Gestational Age Newborn Study from 2002–2004 were evaluated at age 10 years. We analyzed the relationship between elevated blood concentrations of inflammation-associated proteins in the first 2 weeks (“early elevations”; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 72 publications
(71 reference statements)
3
66
0
3
Order By: Relevance
“…At age 10 years, 966 of these were recruited for an age‐appropriate assessment of cognition, executive function, behaviors, and achievement, 889 (92%) returned for follow up, and 874 were administered the neurocognitive tests (Table 1). Because children who had early systemic inflammation are at heightened risk of cognitive impairment (Kuban et al, 2017), and children who are cognitively impaired do not do well on academic achievement tests, we wanted to restrict our search for any relationship between early systemic inflammation and learning limitations not attributed to global limitation to children who were not cognitively impaired. Thus, the sample for the analyses presented here is restricted to the 666 children who had a DAS‐II verbal IQ ≥ 70 and non‐verbal IQ ≥ 70.…”
Section: Methodsmentioning
confidence: 99%
“…At age 10 years, 966 of these were recruited for an age‐appropriate assessment of cognition, executive function, behaviors, and achievement, 889 (92%) returned for follow up, and 874 were administered the neurocognitive tests (Table 1). Because children who had early systemic inflammation are at heightened risk of cognitive impairment (Kuban et al, 2017), and children who are cognitively impaired do not do well on academic achievement tests, we wanted to restrict our search for any relationship between early systemic inflammation and learning limitations not attributed to global limitation to children who were not cognitively impaired. Thus, the sample for the analyses presented here is restricted to the 666 children who had a DAS‐II verbal IQ ≥ 70 and non‐verbal IQ ≥ 70.…”
Section: Methodsmentioning
confidence: 99%
“…Recent data from the Extremely Low Gestational Age Newborns (ELGANs) study measured pro‐inflammatory cytokine patterns in whole blood of preterm infants <28 weeks gestation in the first month of life and demonstrated that elevated systemic levels of pro‐inflammatory cytokines are associated with adverse neurological outcomes up to the age of 10 years (Kuban et al . ), and that both antenatal and postnatal inflammation play a role (Yanni et al . ).…”
Section: The Global Burden Of Hypoxic–ischaemic Brain Injurymentioning
confidence: 99%
“…The cause of neurodevelopmental impairment after preterm birth is multifactorial. However, there is compelling evidence that exposure to perinatal infection/inflammation is strongly associated with preterm birth and impaired neurodevelopment [2][3][4]. In recent studies, long-term neurodevelopmental impairment was associated with diffuse injury in the white matter tracts, with evidence of chronic gliosis and impaired oligodendrocyte maturation, but limited cell loss [5,6].…”
Section: Introductionmentioning
confidence: 99%